Heterogeneous effects of trade openness on wages in the Philippines evidence from industry, area, and educational levels perspectives - Ramas, River M.
Trade is a significant driver of economic growth and development, with far-reaching implications for wages and labor markets. However, empirical studies on the effects of trade openness on wages in the Philippines, particularly at the industry, area, and educational level, remain limited. This paper fills a research gap by examining the relationship between trade openness and wages in the Philippines. Following Perez-Silva & Krivonos (2021), this study explores the nuanced effects of trade openness on wages in the country. The findings reveal an overall positive association between trade openness and wages, with a 1% increase in trade openness corresponding to a 0.458% increase in wages, on average. However, the effects vary across industries, areas, and educational levels, highlighting the need for further research to understand the nuances of the trade-wage relationship in the Philippine context. The implications for policy formulation emphasize the importance of targeted interventions to address the diverse effects of trade on wages, promoting inclusive growth and providing support to workers impacted by trade dynamics.